2017
DOI: 10.1016/j.apme.2017.02.008
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Postpartum Haemorrhage in Patients with Severe Preeclampsia Using Carbetocin Versus Misoprostol

Abstract: Background: Haemorrhage is a leading cause of maternal death worldwide, accounting for over 30% of maternal deaths in Africa and Asia. Postpartum bleeding was also 1.6 times higher in women with preeclampsia than in normotensive women.Objective: We aimed to prevent postpartum haemorrhage in patients with severe preeclampsia by using either carbetocin or misoprostol. The primary outcome was postpartum haemorrhage (blood loss of ≥500 ml) while our secondary outcomes included use of other uterotonics, blood trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 15 publications
0
9
1
Order By: Relevance
“…In addition, Attilakos et al [16] researchers found that there were no significant differences in the secondary outcomes, including major PPH and blood transfusions. This is contrary to other results where the need for blood transfusion was found to be higher with misoprostol as compared to carbetocin [23] . Also, Abd El-Wahab et al [21] showed that the need for blood transfusion was different as in carbetocin group there wasn't any patient need blood transfusion versus 3 cases in misoprostol group need for blood transfusion.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In addition, Attilakos et al [16] researchers found that there were no significant differences in the secondary outcomes, including major PPH and blood transfusions. This is contrary to other results where the need for blood transfusion was found to be higher with misoprostol as compared to carbetocin [23] . Also, Abd El-Wahab et al [21] showed that the need for blood transfusion was different as in carbetocin group there wasn't any patient need blood transfusion versus 3 cases in misoprostol group need for blood transfusion.…”
Section: Discussioncontrasting
confidence: 99%
“…Ibrahim and Saad [23] performed prospective, randomized study and found that the need of extrauterotonic drugs and need for blood transfusion was significantly higher with misoprostol than carbetocin. In the same line, Larciprete et al [24] compared carbetocin and oxytocin in high-risk patients who underwent caesarean section and they noted that carbetocin was associated with lower use of additional uterotonics.…”
Section: Discussionmentioning
confidence: 99%
“…The third study (RCT) was performed in Benha, Egypt [ 22 ] by Mohamad Ibrahim and it included 60 severe pre-eclamptic patients in 2 groups (carbetocin [ n = 30] and misoprostol [ n = 30]). Women with severe preeclampsia and singleton baby, gestational age > 28 weeks and vaginal delivery were included in this study.…”
Section: Resultsmentioning
confidence: 99%
“…Need for blood transfusion and manual removal of the placenta were not significantly different between women who received carbetocin and those who received misoprostol, irrespective of whether the women had cesarean section or vaginal delivery (RR 0.57, 95% CI 0.21–1.58, study 21, 422 participants), (RR 0.73, 95% 0.48 to 1.1, studies 20, 22, 245 participants) respectively. There was no maternal death or ICU admission in the three studies [ 20 22 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation